HAK ASASI MANUSIA (HAM) DALAM DUNIA ISLAM (Telaah terhadap Konsep dan Dinamika HAM di Indonesia) - Reksiana Reksiana (STIT AL-AMIN KREO TANGERANG, 2021)
This paper study how the history, concepts and dynamics of human rights in the world. At the end of the paper it can be said clearly that human rights have bleak times and the upheaval of human rights does not escape the mission and interests of each party, but as time goes on human rights continue to develop with the emergence of the Independent Human Rights Commission created by the OIC in the development of human rights issues in the world in the future and specifically in the Muslim community. It’s hoped that the IPHRC will become a dialogical forum between the various human rights debates and Islamic law or, on the contrary, this IPHRC organization will actually sharpen the discourse, the journey of human rights and Islamic law which further enhances dichotomous views. Continuous discussion between two entities, Islamic law (sharia) and human rights must always be a concern of all groups, in order to open up wider opportunities for mutual understanding to achieve progress and protection of human rights itself. In addition, efforts are also needed to overcome these challenges and challenges by governments, institutions and organizations that can be involved.